2016
DOI: 10.1016/j.jid.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Mineralocorticoid Receptor Plays Beneficial and Adverse Effects in Skin and Mediates Glucocorticoid Responses

Abstract: Glucocorticoids (GCs) regulate skin homeostasis and combat cutaneous inflammatory diseases; however, adverse effects of chronic GC treatments limit their therapeutic use. GCs bind and activate the GC receptor and the mineralocorticoid receptor (MR), transcription factors that recognize identical hormone responsive elements. Whether epidermal MR mediates beneficial or deleterious GC effects is of great interest for improving GC-based skin therapies. MR epidermal knockout mice exhibited increased keratinocyte pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 47 publications
9
62
1
15
Order By: Relevance
“…(Figure 3d). Of note, as mineralcorticoid receptor has been implicated in glucocorticoid responses in skin (Boix et al , 2016), mRNA expression of the mineralcorticoid receptor was also decreased in PP compared to PN and NN skin (2.2-fold decreased, p<0.01).…”
Section: Resultsmentioning
confidence: 95%
“…(Figure 3d). Of note, as mineralcorticoid receptor has been implicated in glucocorticoid responses in skin (Boix et al , 2016), mRNA expression of the mineralcorticoid receptor was also decreased in PP compared to PN and NN skin (2.2-fold decreased, p<0.01).…”
Section: Resultsmentioning
confidence: 95%
“…Glucocorticoids bind and activate two closely related receptors, the GC receptor (GR) and the mineralocorticoid receptor (MR). Our recent work using genetic and pharmacological approaches in mouse skin and healthy skin of volunteers and human skin explants has shown that MR inactivation ameliorates GC‐induced skin atrophy . In both settings, MR blockade improved the epidermal thinning partially reversing the keratinocyte proliferation inhibition induced by topical GC treatments .…”
Section: Introductionmentioning
confidence: 99%
“…One complication is that Dex also activates the mineralocorticoid receptor (MR) albeit with reduced affinity and efficiency [45]. MR in the epidermis does play an important role, mediates some glucocorticoid effects and is required along with GR for proper keratinocyte differentiation [46]. While MR, just like GR, is itself an Hsp90 client [47], its p23 dependence is less well understood.…”
Section: Discussionmentioning
confidence: 99%